2021
DOI: 10.31729/jnma.6281
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay in the Emergency Department during COVID-19 Pandemic in a Tertiary Care Hospital: A Descriptive Cross-sectional Study

Abstract: Introduction: Emergency Department overcrowding has become worsening problem internationally which may affect patient, emergency department efficiency and quality of care and this may lead to increased risk of in hospital mortality, higher costs, medical errors and longer times to treatment. With this pandemic COVID-19 likely to go on for months, if not a year or longer, the Emergency Department should be prepared for large influx of patients infected with COVID-19. The aim of this study is to find-out the len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In the current COVID-19 situation, strict screening and careful admission are necessary. Therefore, as seen in prior literature, [ 12 14 ] our study found that the length of stay in the resuscitation area was longer than before the pandemic.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the current COVID-19 situation, strict screening and careful admission are necessary. Therefore, as seen in prior literature, [ 12 14 ] our study found that the length of stay in the resuscitation area was longer than before the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…This study found that the LOS in the resuscitation area during the COVID-19 period was longer than in the pre-COVID-19 period. Studies in other regions have also shown the problem [ 12 14 ]. The reasons for crowding in the emergency department or resuscitation area can be divided into three aspects: input, throughput, and output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the duplex renal collecting system and ectopic ureter insertion is well-established [ 1 , 2 ]. Although congenital genitourinary abnormalities are usually detected during childhood, incidentally, or due to underlying symptoms or medical complications, a few cases might not be diagnosed/treated until adulthood [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as COVID-19 continues to spread and the number of cases continues to rise, the number of emergency medical service (EMS) calls increases as well [5]. The length of stay in the ED has increased significantly during the pandemic compared to pre-pandemic times [6] and hospitalizations for critically ill patients in the ED have doubled [7]. Consequently, issues with the transportation of emergency patients to the ED have been reported in many countries [8,9].…”
Section: Introductionmentioning
confidence: 99%